Selective laser melting of Ti6Al4V sub-millimetric cellular structures: prediction of dimensional deviations and mechanical performance - Bartolomeu, Flávio (2021)
Ti6Al4V sub-millimetric cellular structures arise as promising solutions concerning the progress of conventional orthopedic implants due to its ability to address a combination of mechanical, physical and topological properties. Such ability can improve the interaction between implant materials and surrounding bone leading to longterm successful orthopedic implants. Selective Laser Melting (SLM) capability to produce high quality Ti6Al4V porous implants is in great demand towards orthopedic biomaterials. In this study, Ti6Al4V cellular structures were designed, modeled, SLM produced and characterized targeting orthopedic implants. For that purpose, a set of tools is proposed to overcome SLM limited accuracy to produce porous biomaterials with desired dimensions and mechanical properties. Morphological analyses were performed to evaluate the dimensional deviations noticed between the model CAD and the SLM produced structures. Tensile tests were carried out to estimate the elastic modulus of the Ti6Al4V cellular structures. The present work proposes a design methodology showing the linear correlations found for the dimensions, the porosity and the elastic modulus when comparing the model CAD designs with Ti6Al4V structures by SLM.